Amoxicillin Induced Immediate Allergic Reaction– A Case Report - Malpani, Ashok Kumar; Miya, Riyaz; Teja, Praveen; Reddy, Brahmadi Shankar (Indian Journal of Pharmacy Practice)
Amongst antibiotics, amoxicillin is oftentimes prescribed to oppugn array of infections. Penicllins are well recognised for their drug induced cutaneous eruptions substantially in paediatric population. This case is being promulgated to strengthen the evidence against amoxicillin induced skin reactions.
Keywords: Amoxicillin; Cutaneous; Penicillin; Paediatrics.